Soil Distribution in Nepal - Gurung, Sher Bahadur (NUTA Journal, 2020)
Soil is the important natural recourse for living things of the world and regulates its ecosystem. Soil types are depending on physiographic and climatic factors. The study discussed soil types of Nepal prepared by Land Resource Mapping Project (LRMP) based on world reference base developed by Food and Agriculture Organization of the United States (FAO) and Soil and Terrain (SOTER) soil type of Nepal by ISRIC-World soil Information based on universal soil classification system developed by United State Department of Agriculture (USDA) using Geographic information system (GIS). According to LRMP the soil types of Nepal are as follow: Dystrochrepts Haplumbrepts Haplustalfs, Dystrochrepts Haplustalfs Rhodustalfs, Haplumbrepts Dystrochrepts Cryumbrepts, Udipsamments Dystrochrepts Rhodustalfs, Glaciated Mountain, Haplaquents Haplaqepts Eutrocrepts, Udorthents Ustorthents Haplaquents, Dystrochrepts Halpumbrepts Haplustalfs-calcarious Materials, Rhodustalfs Dystrochrepts Haplustalfs, Dystrochrepts Eutrochrepts Argiudolls, Dystrochrepts Hapludalfs Haplustalfs-Calcarious Materials, Haplaquents Psammaquents Ustorthents, Haplaquents Eutrocrepts Heplaquents-calcareous Materials and Haplaquepts Dystrochrepts Haplaquents covering four soil order i.e. Entisols, Inseptisols. Mollisols and Alfisols. According the SOTER map, the soil types are as follow: Gelic LEPTOSOLS, Eutric CAMBISOLS, Eutric REGOSOLS, Humic CAMBISOLS, Chromic CAMBISOLS, Dystric REGOSOLS, Eutric GLEYSOLS Calcaric, PHAEOZEMS, Gleyic CAMBISOLS, Haplic PHAEOZEMS, Calcaric FLUVISOLS and other are glacier, ice, rock croup, lake and water. These types of soils are controlled by physiography and climatic factors. The SOTER soil types are more familiar than LRMP soil map although in LRMP soil map is useful to understand the soil characteristics and soil forming processes of Nepal. The soil degradation mitigation and adaptive strategies should consider the soil diversity types and its controlling factors such as physiography and climate.